2005
DOI: 10.1515/hf.2005.105
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of earlywood and latewood of Pinus radiata D. Don: Anisotropic shrinkage, equilibrium moisture content and fibre saturation point

Abstract: Anisotropic shrinkage (tangential and longitudinal), equilibrium moisture content (EMC) and fibre saturation point (FSP) were measured for separated earlywood (EW) and latewood (LW) of a 0.75-m-long log of 20-year old Pinus radiata that was cut at breast height from a selected tree in the forest of Central North Island, New Zealand. The experimental results have shown that at 12% moisture content (MC), tangential shrinkage was 3.23% for EW and 3.90% for LW, with an overall average of 3.56%. Longitudinal shrink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 4 publications
2
15
1
Order By: Relevance
“…The structure of the wood did not influence their results as specimens were conditioned to equilibrium MC before measuring electrical MC or rather large specimens were used in outdoor conditions. Taking into account these conditions, the MC distribution in the core of the specimens is more or less even and the MC value of high and low density zone is close to each other when the MC is below FSP [25]. Therefore, the electrical MC is in a good agreement with the gravimetrical MC especially when the MC is below 30% [5].…”
Section: Of Solid Woodmentioning
confidence: 69%
“…The structure of the wood did not influence their results as specimens were conditioned to equilibrium MC before measuring electrical MC or rather large specimens were used in outdoor conditions. Taking into account these conditions, the MC distribution in the core of the specimens is more or less even and the MC value of high and low density zone is close to each other when the MC is below FSP [25]. Therefore, the electrical MC is in a good agreement with the gravimetrical MC especially when the MC is below 30% [5].…”
Section: Of Solid Woodmentioning
confidence: 69%
“…Because wood disks are round, the practical shrinkage strain in a tangential direction is closer to the radial strain as one approaches the center of the disk; specifically, the difference in the practical shrinkage strain in the tangential and radial directions is proportional to the radius. Pang and Herritsch noted that tangential shrinkage increased from the pith to the seventh growth ring both in earlywood and latewood [21]. In addition, at each level of moisture content, the practical shrinkage strain in heartwood was higher than in sapwood because of the higher density for heartwood.…”
Section: Practical Shrinkage Strainmentioning
confidence: 97%
“…Early investigations indicated 0.9% higher MC grav in LW than in EW for Scots pine (Pinus sylvestris) (Boutelje 1962) and fir (Abies alba) (Popper and Bariska 1972). Pang and Herritsch (2005) found a MC grav increase of 0.1% to 0.6% for Radiata pine (Pinus radiata) and attributed this to an increased content in hemicelluloses. Moon et al (2010) found a MC grav increase of 1% for Loblolly pine (Pinus taeda).…”
Section: Introductionmentioning
confidence: 99%